2014
DOI: 10.1371/journal.pone.0106689
|View full text |Cite
|
Sign up to set email alerts
|

Illumina TruSeq Synthetic Long-Reads Empower De Novo Assembly and Resolve Complex, Highly-Repetitive Transposable Elements

Abstract: High-throughput DNA sequencing technologies have revolutionized genomic analysis, including the de novo assembly of whole genomes. Nevertheless, assembly of complex genomes remains challenging, in part due to the presence of dispersed repeats which introduce ambiguity during genome reconstruction. Transposable elements (TEs) can be particularly problematic, especially for TE families exhibiting high sequence identity, high copy number, or complex genomic arrangements. While TEs strongly affect genome function … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
167
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 61 publications
(91 reference statements)
0
167
3
1
Order By: Relevance
“…High-resolution structural characterization (34,35) will be required to fully explore the precise influence of chromosomal rearrangements on gene flow. For now, our study provides the first empirical evidence connecting gene flow and chromosomal rearrangements in equids.…”
Section: Resultsmentioning
confidence: 99%
“…High-resolution structural characterization (34,35) will be required to fully explore the precise influence of chromosomal rearrangements on gene flow. For now, our study provides the first empirical evidence connecting gene flow and chromosomal rearrangements in equids.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to dilution-based synthetic read approaches [17][18][19], the intramolecular circularization step in our protocol makes it possible to prepare a library in a single tube. We further exploited this property to allow multiple samples to be combined and prepared in the same mixture, yielding considerable savings in cost and time.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that coverage is uneven across barcode groups, varying by up to two orders of magnitude (S9 Fig). As a result of their common reliance on long-range PCR, our method and the TruSeq Long Reads approach may exhibit bias against regions of the genome due to secondary structure or GC content, though we do not observe GC bias in the datasets presented here (S7 Fig). Synthetic read methods also fail to assemble regions containing short repeats, which can be accurately sequenced by true long read methods (McCoy et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Illumina TruSeq protocol is able to produce 10-kbp long reads, retaining the benefits of the highly accurate and cost-effective Illumina technology (Kuleshov et al 2014) and enabling human genome phasing (Kuleshov et al 2014) and de novo assembly of complex genomes (Voskoboynik et al 2013;McCoy et al 2014).…”
mentioning
confidence: 99%